Analysis of Solving Galerkin Finite Element Methods with Symmetric Pressure Stabilization for the Unsteady Navier-Stokes Equations Using Conforming Equal Order Interpolation (Advances in Applied Mathematics and Mechanics, 2018)
This paper gives analysis of a semi-discrete scheme using equal order interpolationto solve unsteady Navier-Stokes equations. A unified pressure stabilizedterm is added to our scheme. We proved the uniform error estimates with respect tothe Reynolds number, provided the exact solution is smooth.